Production and water relations of peanut irrigated with brackish water under pulse and continuous drip - Alan H. S. Silva; José A. Santos Júnior; Manassés M. da Silva; Gerônimo F. da Silva; Ruana I. F. Cruz; Salomão de S. Medeiros; Martiliana M. Freire (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT An efficient water management in irrigation is essential to optimize water efficiency, especially when using brackish water. Thus, the present study was carried out aiming to analyze gas exchanges, pod production, and the water status of peanut plants under increasing levels of salinity (electrical conductivity of 0.12, 1.6, 2.8, 4.0, and 5.2 dS m-1) and the application of the irrigation depth via pulses. A randomized block design in a 5 × 2 factorial scheme was used with four replications, adding up to forty experimental units. The experiment was carried out in drainage lysimeters, at the Federal Rural University of Pernambuco, in open fields from September to November 2019. It was concluded that the use of pulse drip irrigation did not mitigate the deleterious effect of salinity but promoted higher grain and pod production compared to continuous drip irrigation. It was also found that the use of brackish water via pulse drip irrigation promotes greater water use efficiency compared to continuous drip irrigation, and that the increase in the electrical conductivity of the water reduced the water, pressure, and osmotic potentials, along with the osmotic adjustment.